Comparative proteomic analysis of phenol degradation process by Arthrobacter. (May 2016) - Li, Fei; Song, Wenjun; Wei, Jiping; Liu, Chongji; Yu, Chunhua
Abstract: Phenol is a widespread environmental pollutant due to their broad usage and applications, and presence in many industrial effluents. To date, bacterial degradation of phenol remains to be the preferred method for its removal and remediation. Although the degradation pathway has been extensively studied, the variations in the level of expression of the key enzymes during catabolism are still not quantitatively understood. An explicit quantitative expression helps us know the degradation process in detail. It is important and valuable for us to further understand mechanisms underlying phenol degradation. In this study, we used iTRAQ-based comparative proteomics analysis approach to determine variations in expression and regulation of key enzymes in Arthrobacter during phenol degradation. We propose that the phenol biodegradation pathway is mainly determined by 5 pivotal enzymes, which belonged to 3-oxoadipate pathway and tricarboxylic acid cycle. Arthrobacter mainly degrades phenol through 3-oxoadipate pathway, which makes the pathway of this strain for degrading the toxic compound clearer. These findings provide new insights into phenol biodegradation process and would help us understand the step by step stages of this metabolic pathway. Highlights: The main phenol degradation pathway in Arthrobacter was determined by iTRAQ method. The whole enzymes system in phenol degradation pathway was detected in Arthrobacter. The significant expressions level of 3 proteins indicate they are the key enzymes in phenol degradation process.